Foreign experience of regulation of public procurement (Journal of Economic Research & Business Administration, 2018)
The purpose of this article is to review and study the foreign experience of regulation of public procurement, the use of effective parties in the development of public procurement in our country. Рublic procurement is a powerful factor affecting the level of economic development of any country. Public procurement abroad contributes to the development of various sectors of the economy, stimulate innovative programs, support the products of local producers, ensure the implementation of some social processes. Foreign public procurement system is considered by the authors as one of the main elements of the system of support of economic and social stability, as well as a tool for regulating the food market. The factors promoting and hindering the implementation of sustainable public procurement are also highlighted. The study used General methods of studying economic phenomena. The theoretical significance of the study is to study the foreign experience of regulation of public procurement and the introduction of its effective sides in the public procurement system of the country. Foreign experience in the regulation of public procurement can be used in the process of training for students of economic specialties.